Case report: Subacute transverse myelitis with gait preservation secondary to Lyme disease and a review of the literature - Colot, Charlotte; Adler, Catherine; Mignon, Céline; De Leucio, Alessandro; Jissendi, Patrice; Fonteyne, Jean; Aeby, Alec (Frontiers in Pediatrics, 2023)
Subacute presentation with gait preservation is rare in the initial presentation of transverse myelitis (TM) in children. Lyme TM is poorly described in the literature. We present the case of a 10 year-old boy who presented neck pain with irradiation in the upper limbs for 13 days accompanied by a right latero-torticollis. Magnetic resonance imaging (MRI) of the spine showed an hypersignal in the centromedullary T2 weighted image (WI) between C1 and C7 suggestive of cervical transverse myelitis. Lumbar puncture revealed pleocytosis and proteinorachia. Borrelia IgG in the blood and intrathecal IgG synthesis were positive, confirming the diagnosis of TM secondary to Lyme disease. The patient was treated with high dose steroids and antibiotics and recovered completely. After a review of the clinical features of the eight previously published pediatrics cases, we can conclude that Lyme TM has usually a subacute clinical presentation and is frequently limited to the cervical spine with pure sensory symptoms and gait preservation. Moreover, acute and chronic sphincter dysfunction is rare and recovery is usually complete.